Polioencephalomalacia (PEM) in calves associated with excess sulfur intake - Withoeft J.A.* (2019)
© 2019 Pesquisa Veterinaria Brasileira. All rights reserved.Polioencephalomalacia (PEM) is the morphological characterization for softening of brain gray matter, and excess sulfur intake is one of its main causes. This study describes an outbreak of this disease in 1-to-3-month-old calves in a farm located in Santa Catarina state, Brazil. The herd consisted of 27 Jersey male calves whose diet was composed of initial feed, ground whole corn, and mineral salt. From this herd, 10 animals became ill, showing signs of apathy, anorexia and blindness, evolving to generalized weakness and death. Necropsy was performed in three of these animals, which showed flattening of the cerebral convolutions in addition to softened, yellowish areas in the cerebral cortex. Histopathological examination revealed deep laminar necrosis associated with perineuronal and perivascular edema, as well as neurons with wrinkled, eosinophilic, or vacuolated cytoplasm. The following sulfur doses were observed: 8,010mg/kg in corn, 6,385mg/kg in initial feed, 1,060mg/kg in mineral salt and 2.3mg/L in water, reaching dose values far above the accepted, totaling a daily intake of approximately 6,533.5mg sulfur/animal/day. As differential diagnosis, lead was dosed in the kidneys and liver of the three calves, with negative results. Also, the calf that sickened last was treated with 20mg/kg thiamin and 0.2mg/kg dexamethasone (IM; QID) for three days and eventually recovered. According to anatomopathological findings, excess sulfur intake and therapeutic diagnosis, sulfur poisoning was suggested as the cause of PEM in these 1-to-3-month-old calves. Occurrence of PEM is rare in calves at such a young age.